Meningkatkan Kemampuan Literasi Dasar Melalui Program Literasi Dusun Menggunakan Empat Teknik Menentukan Level Kemampuan Membaca pada Siswa Sekolah Dasar di Desa Jenggala - Kurniawan, Azril; Musafir, Musafir; Habiburrahman, Lalu; Akrom, Muhamad; Huryati, Huryati; Hotimah, Nurul; Zulfiani, Nila (Jurnal Pengabdian Masyarakat Sains Indonesia, 2024)
The purpose of this community service is to improve students' basic literacy skills through a hamlet literacy program using four techniques to determine the level of reading ability of elementary school students in Jenggala Village in 2024. The research method used in this community service is qualitative descriptive. The subjects guided by KKN STKIP Hamzar students in Jenggala Village were 15 elementary school students. Data collection techniques used observation, interview, and documentation techniques. The results of the community service show that the basic literacy skills of 15 elementary school students in Jenggala Village have increased, where the 15 children are able to read letters, words, stories and paragraphs. This success is due to the routine of KKN STKIP Hamzar students in guiding and precisely the tools used through the hamlet literacy program that is implemented.